2017
DOI: 10.1111/jfb.13316
|View full text |Cite
|
Sign up to set email alerts
|

Influence of euthanasia method on blood and gill variables in normoxic and hypoxicGulf killifishFundulus grandis

Abstract: In many experiments, euthanasia, or humane killing, of animals is necessary. Some methods of euthanasia cause death through cessation of respiratory or cardiovascular systems, causing oxygen levels of blood and tissues to drop. For experiments where the goal is to measure the effects of environmental low oxygen (hypoxia), the choice of euthanasia technique, therefore, may confound the results. This study examined the effects of four euthanasia methods commonly used in fish biology (overdose of MS-222, overdose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The main goal of this study was to determine the levels of HIF1α protein and HIF1A mRNA in tissues of the Gulf killifish, F. grandis , when exposed to short-term hypoxia (6 or 24 h at 1 mg O 2 l −1 or ∼13% of air-saturation at 25°C). These exposure conditions led to higher hematocrit, blood glucose, and blood lactate, all of which are typical responses of fish to low oxygen availability ( Gallaugher and Farrell, 1998 ; Virani and Rees, 2000 ; Larter and Rees, 2017 ; Richards, 2009 ). The increase in hematocrit was mainly accounted for by RBC swelling, rather than an increase in RBC number.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main goal of this study was to determine the levels of HIF1α protein and HIF1A mRNA in tissues of the Gulf killifish, F. grandis , when exposed to short-term hypoxia (6 or 24 h at 1 mg O 2 l −1 or ∼13% of air-saturation at 25°C). These exposure conditions led to higher hematocrit, blood glucose, and blood lactate, all of which are typical responses of fish to low oxygen availability ( Gallaugher and Farrell, 1998 ; Virani and Rees, 2000 ; Larter and Rees, 2017 ; Richards, 2009 ). The increase in hematocrit was mainly accounted for by RBC swelling, rather than an increase in RBC number.…”
Section: Discussionmentioning
confidence: 99%
“…After 6 or 24 h exposure to either normoxia or hypoxia, fish were netted and immersed in a slurry of aquarium water and ice (<2°C) until loss of equilibrium ( Larter and Rees, 2017 ). Fish were briefly blotted and bled by severing the caudal peduncle.…”
Section: Methodsmentioning
confidence: 99%
“…() reported that freshwater S. salar smolts also had no rise in plasma glucose after a single dose of metomidate (up to 10 mg l −1 ) or AQUI‐S (up to 100 mg l −1 active ingredient). However, behavioural (Pirhonen & Schreck, ; Readman et al ., ; Wong et al ., ) and blood glucose stress responses (Bourne, ; Davis & Griffin, ; Larter & Rees, ; Molinero & Gonzalez, ; Small & Chatakondi, ; Soivio et al ., ; Thomas & Robertson, ; Wagner et al ., ) have been reported in a variety of fish species exposed to a single dose of the same anaesthetics tested in this study. While the role of in‐tank anaesthesia in the reduction of stress has yet to be quantified, it seems likely this methodology plays an important role in minimizing any stress response.…”
Section: Discussionmentioning
confidence: 99%
“…Fish were euthanised and blood was sampled and analysed for haematocrit, plasma cortisol, blood glucose and blood lactate, as described in Larter and Rees (). Briefly, fish were removed from their individual tanks and immediately immersed in an ice‐cold slurry (≤2°C) of liquid and frozen 1 / 3 SW.…”
Section: Methodsmentioning
confidence: 99%
“…After recording haematocrit, the tube was broken at the interface between red blood cells and plasma, and plasma was recovered in a pre‐weighed micro‐centrifuge tube and frozen at −80°C. Plasma cortisol was determined as described previously (Larter & Rees, ). The second whole‐blood sample was transferred to a pre‐weighed micro‐centrifuge tube containing 300 μl of ice‐cold 6% perchloric acid.…”
Section: Methodsmentioning
confidence: 99%